The Role of Serum Metabolomics in Distinguishing Chronic Rhinosinusitis With Nasal Polyp Phenotypes - Xie, Shaobing; Zhang, Hua; Liu, Yongzhen; Gao, Kelei; Zhang, Junyi; Fan, Ruohao; Xie, Shumin; Xie, Zhihai; Wang, Fengjun; Jiang, Weihong (Frontiers in Molecular Biosciences, 2021)
Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a heterogeneous disease characterized by different clinical features and treatment responsiveness. This study aimed to compare the serum metabolomics profiles between eosinophilic CRSwNP (eCRSwNP) and non-eosinophilic CRSwNP (neCRSwNP) and healthy controls (HC) and explore objective biomarkers for distinguishing eCRSwNP before surgery. Methods: Serum samples were collected form 33 neCRSwNP patients, 37 eCRSwNP patients and 29 HC. Serum metabolomics profiles were investigated by ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS). Orthogonal partial least square-discriminate analysis (OPLS-DA) was applied to assess the differences between neCRSwNP, eCRSwNP and HC. Results: The analysis results revealed that neCRSwNP, eCRSwNP and HC exhibited distinctive metabolite signatures. In addition, eCRSwNP could be distinguished from neCRSwNP patients basing on their serum metabolic fingerprints, and the top 10 different metabolites were citrulline, choline, linoleic acid, adenosine, glycocholic acid, L-serine, triethanolamine, 4-guanidinobutyric acid, methylmalonic acid and L-methionine, which were related to several most important pathways including arginine and proline metabolism, glycine, serine and threonine metabolism, linoleic acid metabolism, purine metabolism. Among these distinctive metabolites, citrulline, linoleic acid, adenosine and 4-guanidinobutyric acid showed good predictabilities, and the serum levels of citrulline, linoleic acid and adenosine were significantly correlated with tissue eosinophil (T-EOS) percentage and T-EOS count. Conclusion: eCRSwNP patients exhibited distinctive serum metabolomics signatures compared to neCRSwNP patients and HC. These results suggested that metabolomics profiles might provide novel insights into pathophysiological mechanisms of eCRSwNP and contribute to its prediction.